Situation Report: Hungary, 19 June 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Attempt to Increase the Scope of Private Enterprise in Domestic Trade Hungarian-Japanese Economic Relations Expanded 1981 Book Week Poet Janos Pilinszky Dies New Book Describes Desolate Life in Hostels for Women First Code for Ethical Advertising